The Impact of Intellectual Capital on Firm Performance of the Turkish Real Estate Companies Before and After the Crisis - Nassar, Sedeaq (European Scientific Journal, ESJ, 2018)
Purpose- The main purpose of this study is to find the impact of intellectual capital on firm performance of real estate companies listed in Borsa Istanbul, using data of 27 listed companies over the period 2004-2015. Value Added Intellectual Coefficient (VAIC) method is utilized as a measure of intellectual capital (IC). Methodology- An OLS regression is used to examine the impact of intellectual capital (VAIC); Human capital efficiency (HCE), Structural capital efficiency (SCE), and Capital employed efficiency (CEE) on market, productivity, and financial performance. Findings- The findings show that SCE consider as a key role of value creation in real estate companies where has a positive significant relation with MB, ROE, and EPS before the crisis and with ROA and ROE after the crisis. HCE show a positive significant relation with ROA and ROE before the crisis and a negative significant association with MBand ATO after the crisis. CEE show a negative significant impact on ATO after the crisis. VAIC shows a significant positive impact on ROA, ROE, and EPS before the crisis, while it has the same relation with ROE after the crisis. Conclusion- Although the good result of using intellectual capital for value creation, real estate Turkish companies still weakly depend on its intellectual capital.